2015
DOI: 10.1007/s12311-015-0670-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Contribution to Context Processing in Extinction Learning and Recall

Abstract: Whereas acquisition of new associations is considered largely independent of the context, context dependency is a hallmark of extinction of the learned associations. The hippocampus and the prefrontal cortex are known to be involved in context processing during extinction learning and recall. Although the cerebellum has known functional and anatomic connections to the hippocampus and the prefrontal cortex, cerebellar contributions to context processing of extinction have rarely been studied. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Many other brain areas have been implicated in spatial processing including visual areas [29], parietal areas [30], auditory areas [31], the amygdala [32], the striatum [33], the mPFC [34], and even the cerebellum [35]. When analyzing neural networks involved in cognitive processes, some areas play specific roles and others may serve as more central processing nodes.…”
Section: Processing and Encoding Information About Space And Contextmentioning
confidence: 99%
“…Many other brain areas have been implicated in spatial processing including visual areas [29], parietal areas [30], auditory areas [31], the amygdala [32], the striatum [33], the mPFC [34], and even the cerebellum [35]. When analyzing neural networks involved in cognitive processes, some areas play specific roles and others may serve as more central processing nodes.…”
Section: Processing and Encoding Information About Space And Contextmentioning
confidence: 99%
“…Renewal effects, however, appeared to be impeded in patients with lesions of the more posterolateral cerebellar hemisphere which has connections with the prefrontal cortex and hippocampus (Bostan et al, 2013;Watson et al, 2019). Furthermore, we found activation of the posterolateral cerebellar hemisphere related to context change during extinction learning of cognitive associations in healthy participants in a 3T fMRI study (Chang et al, 2015). Our findings suggest that the cerebellum contributes to context-related effects of extinction.…”
Section: The Cerebellum As a Frequently Ignored Component Of The Extimentioning
confidence: 49%
“…This does not implicate that there are no neurons in other regions involved in the processes of interest. As another example, recent studies showed that the cerebellum contributes to fear extinction learning (Chang et al, 2015; Utz et al, 2015), an observation that was confirmed by a recent meta-analysis of extinction (Fullana et al, 2018). The cerebellum is however often ignored, or in many human neuroimaging research not even scanned.…”
Section: Challenges and Future Directions In Mapping Fear And Extinctmentioning
confidence: 64%